Evaluating the accuracy of theoretical one‐bond 13C─13C scalar couplings and their ability to predict structure in a natural product. (29th June 2017) - Powell, Jacob; Valenti, Domenic; Bobnar, Harley; Drain, Erika; Elliott, Blaine; Frank, Sydney; McCullough, Tyler; Moore, Sean; Kettring, Andrew; Iuliucci, Robbie; Harper, James K.
Abstract : This study explores the feasibility of using a combination of experimental and theoretical 1‐bond 13 C─ 13 C scalar couplings ( 1 JCC ) to establish structure in organic compounds, including unknowns. Historically, n JCC and n JCH studies have emphasized 2 and 3‐bond couplings, yet 1 JCC couplings exhibit significantly larger variations. Moreover, recent improvements in experimental measurement and data processing methods have made 1 JCC data more available. Herein, an approach is evaluated in which a collection of theoretical structures is created from a partial nuclear magnetic resonance structural characterization. Computed 1 JCC values are compared to experimental data to identify candidates giving the best agreement. This process requires knowledge of the error in theoretical methods, thus the B3LYP, B3PW91, and PBE0 functionals are evaluated by comparing to 27 experimental values from INADEQUATE. Respective errors of ±1.2, ±3.8, and ±2.3 Hz are observed. An initial test of this methodology involves the natural product 5‐methylmellein. In this case, only a single candidate matches experimental data with high statistical confidence. This analysis establishes the intramolecular hydrogen‐bonding arrangement, ring heteroatom identity, and conformation at one position. This approach is then extended to hydroheptelidic acid, a natural product not fully characterized in prior studies. The experimental/theoretical approach proposed herein identifies a single best‐fit structure from among 26 candidates and establishes, for the first time, 1 configuration and 3 conformations to complete the characterization. These results suggest that accurate and complete structural characterizations of many moderately sized organic structures (<800 Da) may be possible using only 1 JCC data. Abstract : The feasibility of characterizing organic structures based exclusively on 1‐bond 13 C─ 13 C scalar couplings ( 1 JCC ) is explored. An approach combining experimental and DFT computed 1 JCC data is employed to select best‐fitting structures from among a large collection of possible candidates. Computed 1 JCC values from model compounds are found to be sufficiently accurate (σ = ±1.2 Hz) that structural analysis of a natural product partially characterized in prior work is completed.